Eksperimentasi Model Pembelajaran Two Stay Two Stray Berbasis Media Roleplay Card terhadap Keaktifan Belajar Pendidikan Agama Islam - Dian Nur hasanah; Ainal Gani; Evi Febriani (WISE Pendidikan Indonesia, 2026)
Learning activity is an essential indicator of successful learning in Islamic Religious Education. However, teacher-centered instructional practices often limit student participation and engagement during classroom learning. This study aims to analyze the effect of the Two Stay Two Stray learning model based on Roleplay Card media on students' learning activity in Islamic Religious Education at SMK Geomatika Bandar Lampung. This study employed a quantitative approach using a quasi-experimental method with a post-test-only control group design. The sample consisted of an experimental class that received instruction through the Two Stay Two Stray learning model based on Roleplay Card media and a control class that received conventional learning. Data were collected through a learning activity questionnaire and analyzed using normality, homogeneity, and independent sample t-test analyses. The results showed a significant difference in learning activity between students in the experimental and control classes, with a significance value of 0.005 (p < 0.05). Students who learned through the Two Stay Two Stray model based on Roleplay Card media demonstrated higher levels of learning activity than those who experienced conventional instruction. These findings indicate that integrating cooperative learning with interactive learning media effectively promotes student engagement and participation in Islamic Religious Education. The study contributes to the development of innovative student-centered learning strategies and provides practical implications for teachers seeking to enhance classroom interaction and learning quality.